Developing applications of bioelectrochemistry: interfaces and electrocatalytic synthesis - Weeks, JR (2020)
The use of biomolecules in chemical applications, such as biosensors, fuel cells and chemical synthesis, is becoming widespread, as improvements are made in biomolecule production, engineering and stability, and cofactor provision. This allows chemists to exploit the selectivity and high activities often observed with biological molecules such as antibodies and enzymes. This thesis concerns the characterisation of (i) an alkanethiol monolayer interface for the immobilisation of antibodies for biosensing, and (ii) the development of an electrochemical cofactor regeneration system for an application in bioelectrosynthesis.